PROBLEMATIKA KEABSAHAN PERKAWINAN BEDA AGAMA: KAJIAN NORMATIF DAN IMPLIKASINYA DALAM PRAKTIK HUKUM DI INDONESIA - Samhan, Sindi Atsari (Universitas Labuhanbatu, 2025)
Interfaith marriage refers to the union between two individuals of different religions and beliefs who agree to establish a marital relationship. In Indonesia, this issue raises legal and sociological debates concerning legal certainty, validity, and the fulfillment of citizens’ constitutional rights. In practice, many interfaith couples seek court approval to obtain a legal determination of their marriage, as reflected in the Surabaya District Court Decision Number 916/Pdt.P/2022/PN.Sby. This study employs a doctrinal method with a comparative law approach to analyze the regulation of interfaith marriage in Indonesia, judicial reasoning in deciding such cases, and its implications for the legal status of children born from these marriages. The findings reveal that interfaith marriage is essentially invalid under Article 2 of Law Number 1 of 1974 on Marriage, which requires that the validity of a marriage must be conducted in accordance with the religion and belief of each party. This creates legal problems, both in terms of legal certainty for the couple and the protection of children’s rights, thereby necessitating further consideration of alternative regulatory frameworks aligned with constitutional principles and Indonesia’s societal pluralism.Keywords: Interfaith Marriage; Legal Validity; Legal Implications